2022
DOI: 10.25135/rfac.6.2202.2365
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating Fluoride, Lead, Arsenic and Cadmium Toxicities in Laboratory Animals and Ruminants through Natural Products

Abstract: Environmental pollutants are considered a serious health problem for humans and animals mainly ruminants in several regions of the world. Previously, many studies have investigated the mechanisms of toxicity of these pollutants on laboratory animals. Afterward, other studies have demonstrated that exposure to environmental pollutants may cause several adverse effects on the ruminant organs, influencing its performance and leading to socio-economic problems for breeders. Fluoride, lead, arsenic, and cadmium are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 117 publications
0
4
0
Order By: Relevance
“…Interestingly, another study documented that hypocalcemia is associated with hypertensive disorders and can increase the risk of numerous problems such as preeclampsia 35 . On the other hand, other studies reported that fluoride can disrupt the antioxidant system via the inhibition of enzymes that have an electropositive cofactor 33 . In this study, the negative correlation between plasma fluoride levels and GPx enzymatic activity in women with pregnancy complications could be due to the binding between fluoride and selenium, which is the key cofactor of GPx.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Interestingly, another study documented that hypocalcemia is associated with hypertensive disorders and can increase the risk of numerous problems such as preeclampsia 35 . On the other hand, other studies reported that fluoride can disrupt the antioxidant system via the inhibition of enzymes that have an electropositive cofactor 33 . In this study, the negative correlation between plasma fluoride levels and GPx enzymatic activity in women with pregnancy complications could be due to the binding between fluoride and selenium, which is the key cofactor of GPx.…”
Section: Resultsmentioning
confidence: 98%
“…Fluoride is a chemical halogen recognized for its high electronegativity. After its absorption, this element is acidified and oxidized, and consequently, it can readily bind to several biological molecules such as cations, proteins, and enzymes to form stable and strong bonds 33 . Additionally, due to its high affinity towards calcium, fluoride reduces calcium absorption, leading to hypocalcemia 34 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has been suggested that there are many groups of enzymes that can be affected by fluoride. More precisely, several enzymes require divalent metal ions as cofactors such as magnesium, calcium, zinc and selenium which have a strong affinity with fluoride, and thus can induce oxidative stress resulting from an inhibitory interaction of these enzymes 13 , 48 , 49 . For that, recent studies focused on supplementation of animals with antioxidants such as gallic acid 50 , quercetin 51 , vitamins 7 , 46 , 52 and medicinal plants 6 , 19 , 26 .…”
Section: Discussionmentioning
confidence: 99%
“…All over the world, many regions are well known for their fluoride contamination. In certain cases, countries such as India, China, Turkey, Morocco, Mexico and Australia, sheep have gained more attention from researchers 12 , 13 . Furthermore, chronic ingestion of fluoride from drinking water, or from roughage growing in soils rich in fluoride or contaminated with fluorinated compounds from volcanic or industrial sources, has a negative impact on the growth and production of sheep 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%